Structured evaluation of a comprehensive microsurgical training program - Mattar, Tiago Guedes da Motta; Santos, Gustavo Bispo dos; Telles, João Paulo Mota; Rezende, Marcelo Rosa de; Wei, Teng Hsiang; Mattar Junior, Rames (Clinics, 2021)
OBJECTIVES: This study proposed a structured microsurgical training program and evaluated it with the assistance of a large sample of surgeons. METHODS: The practical course comprised 16 sessions of approximately 4 hours each. This included two sessions for suturing rubber gloves and two sessions for suturing arteries, veins, and nerves in chicken thighs. The other sessions were performed on the femoral vessels of rats: 5 sessions for end-to-end arterial anastomosis, 5 for end-to-end venous anastomosis, 1 for arterial grafting, and 1 for end-to-side anastomosis. We conducted a structured assessment of the microsurgical skills in each training session. RESULTS: In this study, 89 surgeons were evaluated. The mean scores for the different procedures were as follows: glove suturing, 33.3±0.59; chicken nerve end-to-end anastomosis, 40.3±0.49; chicken artery suturing, 40.9±0.36; chicken vein suturing, 42.3±0.36; graft interposition, 44.8±0.7; and end-to-side anastomosis, 43.7±0.63 (p<0.05 for all). The chicken thigh suturing scores were significantly higher than the rubber gloves suturing scores (p<0.01). There were no differences between scores of the rat artery and chicken thigh suturing procedures (p=0.24). The rat venous anastomosis scores were higher than the rat arterial anastomosis scores (p=0.02), as were graft interposition scores when compared with end-to-end venous anastomosis scores. The end-to-side anastomosis scores did not differ significantly from the grafting scores (p=0.85). The most common errors were inadequate knotting technique and suture rupture due to inadequate technique (both n=88 [98.9%]). CONCLUSION: We propose a 16-step, progressive microsurgical training program to learn the basic microsurgical techniques comprehensively and reliably. The program was evaluated in a large sample of trainees, and it demonstrated the adequacy of the training sequence and results.